Pre‐Print‐Prediction of Morphological Properties for Designed Materials Manufactured via Laser‐Based Powder Bed Fusion of Metals on a Multi‐Laser Machine. Issue 9 (26th June 2022) - Albert, Johannes; Hermann, Oliver; Purschke, Simon; Rule, David; Fleck, Claudia
Abstract : Laser‐based powder bed fusion of metals (PBF‐LB/M) is used to build up configurable open‐porous structures—designed materials (DMs) — out of the nickel‐based superalloy Haynes 282. The main objective is to investigate process parameter influences on DM's morphological properties—relative density (RD), mean pore diameter (PD), mean strut diameter (SD), and surface ratio (SR). For the analysis of hatch distance, laser power, and scan speed—hence line and volume energy—effects a three‐level design of experiment (DoE) is utilized. The resulting process parameter combinations are applied to 77 samples; Multiple repetitions ensured statistical validity for the attained morphological information. The data points were used to elaborate equations for the properties based on the introduced process parameters. The identified relations were implemented into previously developed tolerance equations, which were afterward pre‐print‐predictable. These calculation‐based boundaries were assessed for their validity by comparing them to certain data points from five parameter sets. The RD equation was finally used to analyze the capability of reducing its tolerance width. Here, the formerly identified position‐dependent term was compensated by process parameter adaptions. The effects of the compensation on the other properties were also investigated. Abstract : Laser‐based powder bed fusion of metals (PBF‐LB/M) is employed to build up configurable open‐porous designed materials (DMs) out of the nickel‐based superalloy Haynes 282. Pre‐print‐predictable morphological tolerance equations are formulated by the identification of process parameter influences. Based on these results, parameter‐driven compensation of positioning influences enhances the applicability of DMs.